Pandemic outbreaks in the 21st century : epidemiology, pathogenesis, prevention, and treatment - Viswanath, Buddolla (Academic Press, 2021)
"In the past two decades, several pandemics have ravaged the globe, giving us several lessons on infectious disease epidemiology, the importance of initial detection and characterization of outbreak viruses, the importance of viral epidemic prevention steps, and the importance of modern vaccines. Pandemic Outbreaks in the Twenty-First Century: Epidemiology, Pathogenesis, Prevention, and Treatment summarizes the improvements in the 21st century to overcome / prevent / treat global pandemic with future prospective. Divided into 9 chapters, the book begins with an in-depth introduction to the lessons learned from the first pandemic of the 21st century. It describes the history, present and future in terms of detection, prevention and treatment. Followed by chapters on the outbreak, treatment strategies and clinical management of several infectious diseases like MERS, SARD and COVID 19, Pandemic Outbreaks in the Twenty-First Century: Epidemiology, Pathogenesis, Prevention, and Treatment, presents chapters on immunotherapies and vaccine technologies to combat pandemic outbreak and challenges. The book finishes with a chapter on the current knowledge and technology to control pandemic outbreaks." -- provided by publisher.